Geometric Analysis of the Kanggraksan-Jendral Sudirman Road Section Harjamukti District, Cirebon City, West Java STA 0+000 – STA 2+456 - Isradi, Muhammad; Auliya, Siti Rahma; Rukmana, Istiani Aditia; Kinasih, Reni Karno; Aryapijati, Raden Hendra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Road infrastructure is one of the main components in supporting urban transportation systems. Roads that are well managed can increase mobility efficiency, improve connectivity between areas, and support equitable development. This study was conducted on Jalan Kanggraksan No. 23, Harjamukti District, Cirebon City, West Java, which functions as a primary collector road and has experienced a decline in road quality as a result of high traffic loads. The purpose of this project is to analyze the geometric conditions of the road, determine the required thickness of the pavement layer, and calculate the estimated cost of rehabilitation. The research methods include collecting primary data in the form of average daily traffic surveys (ADT) and secondary data such as traffic growth, design speed, CBR values, rainfall, and pavement material types. Geometric analysis is carried out based on the standards of the Directorate General of Highways using AutoCAD Civil 3D software modelling, including terrain classification, horizontal and vertical bend calculations, superelevation, and sight distance.The results of the analysis show that the ±2.5 km road section has three bends with significant elevation variations, requiring geometric design adjustments to improve safety. A CBR value of 6.5 and annual rainfall of 1900–2500 mm necessitate the use of HRS-BC material with CTB and LFA class A foundations. Pavement thickness analysis resulted in recommendations for a layered structure with a planned lifespan of 12 years, while project cost estimates provided a comprehensive planning basis for sustainable development in the city of Cirebon.